TERAPI BERMAIN LEGO TERHADAP KECEMASAN MASA HOSPITALISASI ANAK PRA SEKOLAH DI RUMKITAL Dr. MIDIYATO SURATANI TANJUNGPINANG - Wasis Pujiati Pujiati (Jurnal Ilmiah Cerebral Medika, 2021)
Anxiety is an unpleasant emotional state that is marked by fear and physical symptoms that are tense and unwanted by the child, so that it will affect his health. Play therapy using lego media is one of the nursing care in children to reduce anxiety and fear. This study aims to determine the effect of play lego therapy on anxiety levels during hospitalization of preschool children. This study uses a quasi-experimental design method with a pre-test and post-test design without control. The sampling technique uses purposive sampling with the number of respondents as many as 24 pre-school children. Data collection tool uses anxiety questionnaire sheets. Wilcoxon test analysis obtained p value of 0,000, which means that there is an influence of playing lego therapy on anxiety during the hospitalization of preschool children at Dr. Rumkital Dr. Midiyato Suratani Tanjungpinang. The results of this study can be a reference that anxiety in children can be reduced by doing lego play therapy and the availability of lego media in a child's room.